{Autonomous Ovarian Cysts in Prepubertal Girls. How Aggressive Should We Be? A Review of the Literature} - Papanikolaou, A.; Michala, L. (Journal of Pediatric and Adolescent Gynecology, 2015)
© 2015 North American Society for Pediatric and Adolescent Gynecology. Study Objective: Precocious pseudopuberty in girls occurs as a result of peripheral estrogen production, most commonly through an autonomous ovarian cyst or in patients with McCune Albright syndrome. Current management is either conservative or surgical. The aim of this study was to identify available literature on presentation, course and treatment of such cases. Design: We performed a medline literature search using the key words 'ovarian autonomous cyst' and 'pseudopuberty'. We included articles published in English, from 1980 to date relating to females aged 2 to 8 years. We excluded papers on other endocrine conditions resulting in premature puberty. Outcome Measures: Type of management, time of resolution, recurrence, progression to Central Precocious Puberty and McCune Albright Syndrome. Results: We identified 9 articles referring to 26 cases of autonomous ovarian cysts. All patients had suppressed LHRH testing and had simple ovarian cysts producing estradiol. Median age of patients was 5 years (range 2.2-8) and size of cyst was 41.5mm (9-60). Ten patients underwent cystectomy or oophorectomy, three were given cyproterone acetate and 13 were managed conservatively. Nine of 13 patients that were managed conservatively and two of those that had a cystectomy had a recurrence. There were three cases that progressed to central precocious puberty (CPP) and one case that was then identified to have McCune Albright (MCA) syndrome. One further case with multiple recurrences was given long term treatment with letrozole. Conclusion: We conclude that although a conservative approach should always be proposed in the first instance, one should be aware of the risk of recurrence and progression to CPP or MCA. Antiestrogen treatment appears promising; however data comparing it with surgical options and particularly long term consequences with regards to future reproductive outcomes are not available.
Keywords: Autonomous ovarian cysts; Peripheral precocious puberty; PPP; Pseudopuberty